Optimizing the Role of Youth Organizations (Karang Taruna) in Empowering Youth Through a Sustainable Governance System in Barru Regency - H, Herman; Nasruddin, Nurfitraeny; Hatimah, Khusnul; Nur, Restu Mayang Sara; D, Dewi (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
This community service activity is entitled "Optimizing the Role of Karang Taruna in Empowering Malay Youth through a Sustainable Governance System," with Karang Taruna of Barru Regency as its partner. The background to this activity is the identification of the problem that many Karang Taruna are not yet optimally developed. The main problems are weak organizational structure, unclear work programs, financial dependence on ceremonial grants, and low youth participation. This situation has stalled Karang Taruna's role in economic empowerment and youth empowerment.The primary objective of this community service is to strengthen Karang Taruna's role as a forum for youth empowerment and to build a transparent, participatory, and collaborative organizational governance system. The proposed solution is the implementation of a "Sustainable Governance System" to improve the orga nization's internal workings to make them more professional and independent.The implementation method will utilize participatory tactics, community bazaars, and capacity building. The program will focus on: (1) Socialization phase for stakeholders; (2) Training phase, which includes materials on organizational development, entrepreneurship, digital technology, and problem-solving; and (3) Mentoring and Evaluation phase for the implementation of sustainable management and programs.